2022
DOI: 10.3390/microorganisms10091846
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Based Exploration of Rhodococcus Species for Plastic-Degrading Genetic Determinants Using Bioinformatic Analysis

Abstract: Plastic polymer waste management is an increasingly prevalent issue. In this paper, Rhodococcus genomes were explored to predict new plastic-degrading enzymes based on recently discovered biodegrading enzymes for diverse plastic polymers. Bioinformatics prediction analyses were conducted using 124 gene products deriving from diverse microorganisms retrieved from databases, literature data, omic-approaches, and functional analyses. The whole results showed the plastic-degrading potential of Rhodococcus genus. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Among the bacterial strains isolated from the 609 day enrichment cultures, a lipase-positive Rhodococcus strain (named A34 strain here) was obtained. Consistent to the existence of potential PE-degrading enzyme genes in Rhodococcus stains based on genome-based exploration, the A34 strain genome had abundant potential PE oxidation and degradation genes. Further time series proteomics data demonstrated the induction and high abundances of extracellular key PE oxidation and depolymerization enzymes such as catalase-peroxidase KatG, multicopper oxidase, lipase, and esterase.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Among the bacterial strains isolated from the 609 day enrichment cultures, a lipase-positive Rhodococcus strain (named A34 strain here) was obtained. Consistent to the existence of potential PE-degrading enzyme genes in Rhodococcus stains based on genome-based exploration, the A34 strain genome had abundant potential PE oxidation and degradation genes. Further time series proteomics data demonstrated the induction and high abundances of extracellular key PE oxidation and depolymerization enzymes such as catalase-peroxidase KatG, multicopper oxidase, lipase, and esterase.…”
Section: Discussionmentioning
confidence: 70%
“…Transcriptomic analysis of Rhodococcus opacus R7 uncovered the potential key genes involved in depolymerization and oxidation of PE such as alkane monooxygenase and cytochrome P450 hydroxylase . Comparative genomics analysis of Rhodococcus genomes indicated the distribution of these potential key plastic degradation-associated genes in Rhodococcus genomes . Despite these findings, in-depth studies on PE-degrading microorganisms and the underlying plastic degradation mechanisms are still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[152,153] The OMICS-level studies have helped in identifying a variety of plastic degrading enzymes (PDEs) associated with the microbes which mediate plastic decomposition utilizing it as a (substrate) source of energy. [154,155] Another critical aspect of protein-PNP interactions is to elucidate the mechanisms of plastic degradation, and the dynamics between plastic degrading enzymes (PDE) and their plastic substrates. Apart from a few studies on PMPs, no other submicron range plastic has been reported as a substrate for the PDEs till date.…”
Section: Bioremediation Of Pnps: Plastic Degrading Proteins and Their...mentioning
confidence: 99%
“…Contemporarily, sequence based analysis is helping in navigating large sequence datasets. Zampolli et al applied sequence-based analysis to determine the genetic determinant of plastic degradation [ 39 ]. Skariyachan et al provided a detailed review about a computational and data driven method applied in the field of plastic degradation [ 40 ].…”
Section: Introductionmentioning
confidence: 99%